(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Recently, the use of polymer-based additives in bitumen modification has increased significantly. In particular, two main types of polymers, elastomer and plastomer, are widely used. Plastomers are commonly used to improve the elastic properties of binders and increase the resistance to permanent deformation of coatings. However, elastomers have been used to improve the fatigue and low-temperature cracking resistance of binders [1]. In order to study the effect on the physical and chemical properties of soft bitumen emulsion, studies were conducted on the use of secondary products, which are elastomeric polymers, and sulfur as a bitumen additive [2]. In many experiments conducted to determine the elasticity, mass loss or wear resistance of bitumen modified with copolymers, it was found that bitumen modified with copolymers and sulfur has a very positive effect on elasticity and wear resistance [3]. Studies have shown that the internal structure of the modified bitumen is homogeneously distributed as a result of the reaction between the metal and the binder, and the cracking problems that may occur between them have disappeared [4].